Kynurenic acid, by targeting α7 nicotinic acetylcholine receptors, modulates extracellular GABA levels in the rat striatum in vivo. Issue 9 (26th February 2013) - Beggiato, Sarah; Antonelli, Tiziana; Tomasini, Maria Cristina; Tanganelli, Sergio; Fuxe, Kjell; Schwarcz, Robert; Ferraro, Luca
Abstract: Kynurenic acid (KYNA) is an astrocyte‐derived non‐competitive antagonist of the α7 nicotinic acetylcholine receptor (α7nAChR) and inhibits the NMDA receptor (NMDAR) competitively. The main aim of the present study was to examine the possible effects of KYNA (30 – 1000 nm ), applied locally by reverse dialysis for 2 h, on extracellular GABA levels in the rat striatum. KYNA concentration‐dependently reduced GABA levels, with 300 nm KYNA causing a maximal reduction to ~60% of baseline concentrations. The effect of KYNA (100 nm ) was prevented by co‐application of galantamine (5 μm ), an agonist at a site of the α7nAChR that is very similar to that targeted by KYNA. Infusion of 7‐chlorokynurenic acid (100 nm ), an NMDAR antagonist acting selectively at the glycineB site of the receptor, affected neither basal GABA levels nor the KYNA‐induced reduction in GABA. Inhibition of endogenous KYNA formation by reverse dialysis of ( S )‐4‐(ethylsulfonyl)benzoylalanine (ESBA; 1 mm ) increased extracellular GABA levels, reaching a peak of 156% of baseline levels after 1 h. Co‐infusion of 100 nm KYNA abolished the effect of ESBA. Qualitatively and quantitatively similar, bi‐directional effects of KYNA on extracellular glutamate were observed in the same microdialysis samples. Taken together, the present findings suggest that fluctuations in endogenous KYNA levels, by modulating α7nAChR function, control extracellular GABA levels in the rat striatum. This effect may be relevant for a number of physiological and pathological processes involving the basal ganglia. Abstract : Kynurenic acid (KYNA) is an astrocyte‐derived, non‐competitive antagonist of the α7 nicotinic acetylcholine receptor (α7nAChR) and inhibits the NMDA receptor (NMDAR) competitively. The present in vivo microdialysis study provides evidence that fluctuations in endogenous KYNA levels tonically modulate extracellular glutamate and GABA levels in the rat striatum, mainly by acting on α7nAChRs. This effects may be relevant for a number of physiological and pathological processes involving the basal ganglia.